Beyond single-dose human mass balance study: minimizing subject confinement and enabling true steady-state assessment with a novel multiple-dose design proposal - Wang, Shuai; Zhao, Weiping; Mandlekar, Sandhya; Pan, Lin; Zhang, Donglu; Khojasteh, Cyrus; Hop, Cornelis E.C.A. (Drug metabolism and disposition, 2025)
Human radiolabeled mass balance studies are typically conducted using a single-dose approach to simplify dose recovery calculations and clearance pathway elucidations. A unique aspect of this clinical study is the need for subject confinement of usually exceeding 10 days in the clinical research unit, which adds up to subject burden and may raise ethical concerns especially in patient populations. Additionally, this method has a major inherent limitation, because single-dose measurements may not accurately represent steady-state conditions, particularly for molecules having time-dependent pharmacokinetics or absorption, distribution, metabolism, and excretion characteristics. To address these challenges, a novel study design implementing multiple fractional [14C]-microtracer doses was proposed and evaluated in a rat proof-of-concept study using [14C]GDC-0334. The results demonstrated that the multiple-dose approach provides robust assessment of circulating metabolite profile and clearance pathways from the analysis of steady-state samples alone. This approach further eliminates the need for sample pooling, thereby simplifying sample preparation and enhancing sample analysis through the use of undiluted samples. Building on the proof-of-concept study, the proposed design for human mass balance studies can also minimize subject confinement time, substantially reducing participant burden, simplifying study logistics, and reducing overall cost. Furthermore, the reduced confinement makes this approach more feasible for implementation in the target patient population. Accordingly, this study supports the adoption of the proposed multiple dose strategy in human mass balance studies to minimize subject confinement, and enable steady-state assessment of circulating drug-related materials and clearance mechanisms, ultimately improving translatability and robustness of study findings. This study validates a novel multiple-dose mass balance design that overcomes the limitations of traditional single-dose methods by enabling evaluation at true steady state. This new approach offers a more reliable and efficient framework for human mass balance studies, with significant benefits including reduced subject confinement, simpler logistics, and more robust sample analysis and data interpretation, ultimately improving the assessment of drug metabolism and clearance. [Display omitted]